Impact of reimplantation technique of supra-aortic branches in total arch replacement on stroke rate and survival: results from the ARCH registry. (8th May 2018) - Schoenhoff, Florian S; Tian, David H; Misfeld, Martin; Perreas, Konstantinos G; Spielvogel, David; Mohr, Friedrich W; Beyersdorf, Friedhelm; Yan, Tristan D; Carrel, Thierry P
Abstract: OBJECTIVES: Our objective was to evaluate the impact of reimplantation techniques of the supra-aortic branches in total arch replacement on the rates of permanent neurological deficit (PND) and survival. METHODS: We identified patients enrolled in the ARCH registry who underwent total arch replacement between 2000 and 2015 with either en bloc or separate reimplantation of the supra-aortic branches. RESULTS: A total of 3345 patients were included in the present analysis. From this cohort, 686 patients underwent en bloc and 2659 patients had separate reimplantation of the supra-aortic branches. Propensity score analysis identified 461 matched patient pairs. In the matched cohort, there were no differences regarding the mortality rate (15.6% vs 15.7%, P  = 0.710) or PND (9.2% vs 12.1%, P  = 0.231). Although separate reimplantation of the supra-aortic branches was not associated with an increased mortality rate on multivariable logistic regression, it increased the risk of PND [odds ratio (OR) 1.56, 95% confidence interval (CI) 1.06–2.29; P  = 0.023]. Propensity-adjusted regression confirmed these findings and found a similar risk for PND with separate reimplantation of the supra-aortic branches (OR 1.50, 95% CI 1.01–2.23; P  = 0.047), although this significance was not found with conditional logistic regression ( P  = 0.20). No significant differences between survival were seen between the 2 matched cohorts (stratified log rank P  = 0.35). CONCLUSIONS: Separate reimplantation of the supra-aortic branches in total arch replacement is a significant predictor of stroke in the overall group, although comparable stroke rates were observed in the matched cohort. The current trend towards separate reimplantation of supra-aortic branches may expose certain subgroups of patients to an increased risk of stroke, e.g. those with a high atherosclerotic burden.